2007
DOI: 10.1029/2006jd007968
|View full text |Cite
|
Sign up to set email alerts
|

GOES Aerosol/Smoke Product (GASP) over North America: Comparisons to AERONET and MODIS observations

Abstract: [1] The GOES Aerosol/Smoke Product (GASP) is a retrieval of the aerosol optical depth (AOD) using visible imagery. The product currently runs operationally at NOAA/NESDIS in near-real time at 30 min intervals. This high temporal resolution is not possible with polar orbiting instruments which produce one daily image. This work evaluates the GASP AOD from the GOES-12 Imager over North America at various temporal and spatial scales based on comparisons with AOD from the Aerosol Robotic Network (AERONET) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 17 publications
6
88
0
Order By: Relevance
“…GASP AOD correlations with the hourly PM 2.5 concentrations were 0.54 for the summer months and 0.50 for 2005, compared with correlations of greater than 0.7 for MODIS Collection 5 and MISR. This result was consistent with Prados et al, 23 in which the authors found that MODIS had a higher correlation than GASP with AERONET AOD observations in a statistical analysis of 10 eastern U.S. sites. Prados et al 23 also found that high GASP AOD measurements (Ͼ0.7) did not appear to correspond with high surface PM 2.5 concentrations; similar results were found in this analysis.…”
Section: Studysupporting
confidence: 92%
See 2 more Smart Citations
“…GASP AOD correlations with the hourly PM 2.5 concentrations were 0.54 for the summer months and 0.50 for 2005, compared with correlations of greater than 0.7 for MODIS Collection 5 and MISR. This result was consistent with Prados et al, 23 in which the authors found that MODIS had a higher correlation than GASP with AERONET AOD observations in a statistical analysis of 10 eastern U.S. sites. Prados et al 23 also found that high GASP AOD measurements (Ͼ0.7) did not appear to correspond with high surface PM 2.5 concentrations; similar results were found in this analysis.…”
Section: Studysupporting
confidence: 92%
“…21 In contrast to the polar-orbiting sensors, which only have one daily daytime overpass for any location on the Earth, the GOES Aerosol and Smoke Product (GASP) is an AOD product provided by the National Oceanic and Atmospheric Administration (NOAA) from the geostationary GOES-12 (East) imager at 15 and 45 min after the hour during daylight hours. 22,23 The AOD is computed from the imager's visible channel (520 -720 nm) at approximately 1-km horizontal resolution. The cloud-masking algorithm is based on the Clouds from AVHRR (CLAVR) algorithm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scans of just North America or the continental United States are much faster. GOES produces an aerosol product (Prados et al, 2007), but these will not be analyzed in this study. Only the cloud mask developed for GOES-R, which has not yet been launched, will be applied to GOES data and used in this study.…”
Section: Modis and Goesmentioning
confidence: 99%
“…For climate, a global perspective is needed Remer et al, 2009). For air quality, even if interest is more regional, there is need for a more complete coverage and higher density of spatial sampling than a network of ground-based in situ monitoring stations can provide (Chu et al, 2003;Prados et al, 2007;Gupta and Christopher, 2009). Both these applications are increasingly relying on satellite retrievals of aerosol information to provide the observational constraints on models, offer new insights on aerosol distributions, and provide day-to-day coverage and accumulated statistics of aerosol properties (Stier et al, 2005;Yu et al, 2006;van Donkelaar et al, 2006van Donkelaar et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%